2017
DOI: 10.14202/vetworld.2017.636-639
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of antibodies to astrovirus in chickens in Grenada, West Indies

Abstract: Aim:Chicken astroviruses (CAstV) are known to cause mild gastroenteritis, growth depression, and even mortality in poultry, especially in chickens, turkeys, and ducks. To the best our knowledge, there is no published information on CAstV in Grenada. This study was conducted to determine the prevalence of astrovirus in chickens in Grenada.Materials and Methods:Blood samples from 366 indigenous chickens and 92 commercial chicken layers were collected from all parishes of the island and tested for antibodies agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Reports have demonstrated that CAstV is prevalent among the broilers' great-grandparents, grandparents, parents, and the commercial flocks of broiler chickens [46,56]. A seroprevalence survey has also demonstrated that the CAstV antibody is widely spread among the parents of commercial laying chickens and layer flocks [57][58][59] and in indigenous or local breeds of chickens [57,58]. Experimental infections demonstrate that 1-day-old SPF chickens are equally susceptible to CAstV infection [4,14,16,18,30,46,[60][61][62] (Table 1).…”
Section: Transmissionmentioning
confidence: 99%
“…Reports have demonstrated that CAstV is prevalent among the broilers' great-grandparents, grandparents, parents, and the commercial flocks of broiler chickens [46,56]. A seroprevalence survey has also demonstrated that the CAstV antibody is widely spread among the parents of commercial laying chickens and layer flocks [57][58][59] and in indigenous or local breeds of chickens [57,58]. Experimental infections demonstrate that 1-day-old SPF chickens are equally susceptible to CAstV infection [4,14,16,18,30,46,[60][61][62] (Table 1).…”
Section: Transmissionmentioning
confidence: 99%
“…7 Studies on Trinidad & Tobago have provided strong evidence for the circulation of important poultry viral and bacterial pathogens in commercial 9 and backyard poultry, 5 including infectious bronchitis virus (IBV; species Avian coronavirus ), Mycoplasma gallisepticum (MG), Mycoplasma synoviae (MS), avian influenza virus (AIV; species Influenza A virus ), avian avulavirus 1 (formerly Newcastle disease virus, NDV), infectious bursal disease virus (IBDV), and Salmonella enterica serovar Enteritidis (SE). Furthermore, there is evidence for West Nile virus (WNV) infections in sentinel chickens in Puerto Rico, 33 chicken astroviruses in Grenada, 30 and Campylobacter spp. in Grenada 32 and Barbados.…”
Section: Introductionmentioning
confidence: 99%
“…Astroviruses, family Astroviridae , have been associated with runting and stunting syndrome, and nephritis in poultry (Sharma et al., 2017a; Zhao et al., 2020). Antibodies to astrovirus were reported in 57.6% of commercial layers and 61.5% of indigenous chickens in Grenada (Sharma et al., 2017a).…”
Section: Rna Viruses Circulating In Terrestrial Animals In the Caribb...mentioning
confidence: 99%